Formulation and Evaluation of Ondansetron HCl Nanoparticles for Transdermal Delivery - Amjed H Noor; Mowafaq M. Ghareeb (College of Pharmacy University of Baghdad, 2020)
Ondansetron HCl (OND) is a potent antiemetic drug used for control of nausea and vomiting associated with cancer chemotherapy. It exhibits only 60 - 70 % of oral bioavailability due to first pass metabolism and has a relative short half-life of 3-5 hours. Poor bioavailability not only leads to the frequent dosing but also shows very poor patient adherence. Hence, in the present study an approach has been made to develop OND nanoparticles using eudragit® RS100 and eudragit® RL100 polymer to control release of OND for transdermal delivery and to improve patient compliance. Six formulas of OND nanoparticles were prepared using nanoprecipitation technique. The particles sizes and zeta potential were measured using zeta-plus analyzer. The particle morphology was also studied using scanning electron microscopy (SEM). The in-vitro release of the drug from the nanoparticles was carried out in phosphate buffer saline pH 7.4. The particle size of the prepared NPs were in nano size which ranged from (95.34 to 275.84 nm) with positive zeta potential. The drug entrapment efficiency was varied with the drug polymer ratio from 41.87% to 78.45%. The SEM showed uniform shape and regularly distributed particle sizes. The in-vitro drug release study exhibited the sustained release of OND with burst release. The cumulative percentage released after 12 hr. were between were 77.89 and 96.01%. Also the transdermal permeation study show that nanoparticles permeate more efficiently than aqueous solution of the drug through the skin by approximately two fold. OND nanoparticles were prepared successfully using nanoprecipitation method. The controlled drug release aimed for transdermal drug delivery could be obtained by using eudragit RS100 and eudragit RL100 polymers which can reduce dosing frequency, decrease side effects and improve patient compliance.